Optimization of the Polymerase Chain Reaction (PCR) amplification of highly variable mitochondrial gene of cytochrome c oxidase I (COI) in Bornean voiceless frogs - Dency Flenny, ak Augustine Gawin. (Universiti Malaysia Sarawak, (UNIMAS), 2003)
Limnonecles kuhlll, and Limnonecles leporinus are the two species of voiceless frogs that can be found in Bomean Island. In this study the site region of cytochrome c oxidase I (COl) of mitochondrial gene in the two Bomcan voiceless frog species were amplified using the Polymerase Chain Reaction (PeR) metllod. The principal of the PeR involved two Oligonucleotide primers that anneal complementary to the 'target' regions of the denatured DNA templates that are to be amplified. Three programmes of PeR that were variod in temperatures and period of each PCR step had been tried to identify the most efficient in amplifying PCR products of both species. From tbe three programmes, 30 cycles of programme B (Initial Denaturation: 96°C for 5 min; Denaturation: 95°C for 45 sec; Annealing: S2°C for I min 30 sec; Extension: 72°C for I min 30 sec; Final extension: 72°C for 10 min) showed the highest percentage of optimal PCR products. As the other programmes, they could amplify products but contaminated with non-specific products or "primer-(bmer". As for annealing temperature, 52°C was sufficient to amplity high quality of PeR products when visualized on eloctropboresis system. Components in 50 !'l reaction mixture were optimized with the optimal concentrations of magnesium, and Taq polymerase "lith 1.5 roM and 0.025-0.05 unitslpl respectively. The rest concentration components were maintained with IX PeR Reaction Buffer, and 0.04 mM of dNTPs mix. The concentrations of used primers were depended on the number of mole of the oligonucleotides. In second amplification, a PCR product with "primcr-dimec" was produced although using the programme B with no adjustment to the optimal concentration of each PCR reagent. Hot-Start PeR method was applied, and mostly it yielded optimal PCR amplification. Further research on the second amplification for the two species should be conducted to detennine either the amplified template, or the cycles are the main cause of the primer-dimer production.